Delovne obremenitve medicinskih sester in zdravstvenih tehnikov - Naka, Sandra (Obzornik zdravstvene nege, 1999)
The article deals with patient classification and respective nursing workload.The findings about the work process of nurses and nursing techniciansin an intensive care unit are presented, as well as the share of direct and indirect nursing care and its distribution as to profiles, premisesand categories of patients.
Keywords: bolniki; Classification; medicinske sestre; Nurses; obremenitve; Patients; Workload; Workplace; zdravstvena nega